Accumulation of phosphorylated TDP‐43 in the cytoplasm of Schwann cells in a case of sporadic amyotrophic lateral sclerosis. Issue 6 (9th August 2020) - Nakamura‐Shindo, Keiko; Sakai, Kenji; Shimizu, Ai; Ishida, Chiho; Yamada, Masahito
Abstract : We report for the first time the presence of phosphorylated transactivation response DNA‐binding protein of 43 kDa (p‐TDP‐43)‐immunoreactive cytoplasmic inclusions in Schwann cells in an autopsy case of sporadic amyotrophic lateral sclerosis (ALS). An 81‐year‐old woman with no family history of neuromuscular disorders noticed difficulty in handling chopsticks due to weakness of the hands. She then developed weakness of the lower and upper limbs and dyspnea. Neurological examination at the age of 83 years revealed disorientation, severe weakness of the facial muscles, tongue, neck and extremities, and fasciculations in the thighs. She exhibited hyperactive jaw jerk and lower limb deep tendon reflexes and normal upper limb deep tendon reflexes, and left extensor plantar response was observed. The patient was diagnosed as having sporadic ALS. An autopsy performed at the age of 84 years revealed widespread p‐TDP‐43‐immunoreactive neuronal and glial cytoplasmic inclusions in the cerebrum, brain stem, and spinal cord, in addition to some Bunina bodies. Moreover, a small number of p‐TDP‐43‐immunoreactive inclusions were found in the facial or accoustic nerve (indistinguishable), spinal cord anterior roots, cauda equina, and peripheral nerves in the dorsal root ganglia. Immunohistochemical staining for p‐TDP‐43 revealed just a few p‐TDP‐43‐immunoreactive inclusions surrounding axons in the cervical and lumbar anterior roots. Double immunofluorescence analysis revealed that these inclusions were co‐localized with S‐100 protein β, suggesting that these inclusions were localized in the cytoplasm of Schwann cells. The peripheral nervous system including Schwann cells may be involved in TDP‐43 pathology in ALS.